1999
DOI: 10.1097/00005072-199906000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Frontotemporal Dementia and Corticobasal Degeneration in a Family with a P301S Mutation in Tau

Abstract: The tau gene has been found to be the locus of dementia with rigidity linked to chromosome 17. Exonic and intronic mutations have been described in a number of families. Here we describe a P301S mutation in exon 10 of the tau gene in a new family. Two members of this family were affected. One individual presented with frontotemporal dementia, whereas his son has corticobasal degeneration, demonstrating that the same primary gene defect in tau can lead to 2 distinct clinical phenotypes. Both individuals develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
292
4
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(309 citation statements)
references
References 0 publications
11
292
4
2
Order By: Relevance
“…A given mutation can lead to different clinical syndromes in an individual family. Thus, mutation P301S in exon 10 of MAPT caused bvFTD in a father and CBD in his son (Bugiani et al 1999), supporting the view that FTD and CBS are part of the same disease spectrum (Kertesz et al 2000).…”
Section: Mutations In Maptmentioning
confidence: 66%
“…A given mutation can lead to different clinical syndromes in an individual family. Thus, mutation P301S in exon 10 of MAPT caused bvFTD in a father and CBD in his son (Bugiani et al 1999), supporting the view that FTD and CBS are part of the same disease spectrum (Kertesz et al 2000).…”
Section: Mutations In Maptmentioning
confidence: 66%
“…Experimental or clinical lesions of the PPRF and riMLF abolish or slow saccades [7,11,12]. Most patients with PSP eventually show slow [24] or absent vertical saccades, and neuropathological studies have demonstrated involvement of the region in which riMLF lies [6,9]. In addition, the localization of pathological changes in riMLF in the midbrain has been reported in two patients with ALS who had supranuclear vertical gaze impairment with slow vertical saccades [2].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genetic studies have revealed that pathologically confirmed cases of PSP, CBD, and FTLD share mutations from a single gene (MAPT) [6,10,21,29,30,36]. Therefore, to encompass the whole spectrum of these disorders, an umbrella term called "Pick complex" has been proposed [17,20,26].…”
Section: Introductionmentioning
confidence: 99%
“…These tangles are composed of all 6 tau isoforms and are structurally and biochemically indistinguishable from those found in Alzheimer's disease (AD) (9,10). For other FTDP-17 mutations, tau is present as paired straight filaments (11) or paired helical filaments with different dimensions than those of AD filaments (12,13). Also the isoform ratio can be different from that found in AD.…”
mentioning
confidence: 99%